THE INFLUENCE OFF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. RAVIDA MANDIRI PALEMBANG - Bukman Lian (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2017)
The goals off this research was for knowing the influence of work motivation and work environment on employee performance at PT. Ravida Mandiri Palembang. The population in this research was the employee of PT. Ravida Mandiri Palembang, there were 150 employees. Sample was determined by simple technique random sampling, with the respondent were 60 employees. Sampling technique that used were questionnaires and documentary. Data analysis that used were simple regression linier analysis, double regression linier analysis, correlation coefficient, determine correlation, test t and test F. Result of discussion obtained the value of test t for work motivation variable obtained t count 18,177 bigger than t table 1,6716 could concluded that there was influence of work motivation on employee performance, while for work environment variable obtained t count 28,429 bigger then t table 1,6716 so could concluded there was influence of work environment on employee performance . Result of test F together obtained F count 208,832 bigger than F table 3,16 so could concluded there was influence of work motivation and work environment on employee performance.